Extra-Nuclear Functions of the Transcription Factor Grainyhead-Like 3 in the Endothelium-Interaction with Endothelial Nitric Oxide Synthase - Kirsten Jander; Jan Greulich; Stefanie Gonnissen; Niloofar Ale-Agha; Christine Goy; Philipp Jakobs; Sabrina Farrokh; Corina Marziano; Swapnil K. Sonkusare; Judith Haendeler; Joachim Altschmied (MDPI AG, 2021)
We previously demonstrated that the transcription factor Grainyhead-like 3 (GRHL3) has essential functions in endothelial cells by inhibiting apoptosis and promoting migration as well as activation of endothelial nitric oxide synthase (eNOS). We now show that a large portion of the protein is localized to myo-endothelial projections of murine arteries suggesting extra-nuclear functions. Therefore, we generated various deletion mutants to identify the nuclear localization signal (NLS) of GRHL3 and assessed potential extra-nuclear functions. Several large-scale deletion mutants were incapable of activating a GRHL3-dependent reporter construct, which could either be due to deficiencies in transcriptional activation or to impaired nuclear import. One of these mutants encompassed a predicted bipartite NLS whose deletion led to the retention of GRHL3 outside the nucleus. Interestingly, this mutant retained functions of the full-length protein as it could still inhibit pathways inducing endothelial cell apoptosis. As apoptosis protection by GRHL3 depends on NO-production, we examined whether GRHL3 could interact with eNOS and showed a direct interaction, which was enhanced with the extra-nuclear GRHL3 variant. The observation that endogenous GRHL3 also interacts with eNOS in intact murine arteries corroborated these findings and substantiated the notion that GRHL3 has important extra-nuclear functions in the endothelium.